2019
DOI: 10.1177/0748730419828068
|View full text |Cite
|
Sign up to set email alerts
|

CikA Modulates the Effect of KaiA on the Period of the Circadian Oscillation in KaiC Phosphorylation

Abstract: A cyanobacterium is the simplest organism to have a circadian clock (Iwasaki and Kondo, 2004). Circadian clocks consist of 3 major components: a central oscillator, an input pathway, and an output pathway (Takahashi, 2004). The central oscillator in cyanobacteria is known as the minimal self-sustained circadian oscillator and is composed of 3 proteins, KaiA, KaiB, and KaiC. The oscillator can be reconstituted in vitro by mixing the Kai proteins with adenosine triphosphate (ATP) and magnesium (Kim et al., 82806… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Cloning, purifications, and phosphorylation assays were performed as described previously without modification (Kaur et al, 2019;Kim et al, 2015). CikA was cloned into the pET41a(+) vector, expressed in Escherichia coli (BL21DE3) and purified with a GST affinity column using the same method as for KaiC (Kim et al, 2015).…”
Section: Phosphorylation Assay Of the Circadian Clock In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning, purifications, and phosphorylation assays were performed as described previously without modification (Kaur et al, 2019;Kim et al, 2015). CikA was cloned into the pET41a(+) vector, expressed in Escherichia coli (BL21DE3) and purified with a GST affinity column using the same method as for KaiC (Kim et al, 2015).…”
Section: Phosphorylation Assay Of the Circadian Clock In Vitromentioning
confidence: 99%
“…Recently, it was reported that CikA directly interacts with the central oscillator, competing with KaiA for binding to KaiB (Tseng et al, 2017). The possibility of its role in the input pathway arises from CikA's nature of competitive binding, since the addition of CikA in the circadian oscillator mixture affects the phosphorylation state of KaiC and shortens its period in vitro (Kaur et al, 2019).…”
mentioning
confidence: 99%
“…Therefore, in addition to regulating rhythms of transcriptional output from the Kai-based PTO (20), SasA also works to directly modulate KaiB association with KaiC to control formation of the nighttime repressive state and robustness of the PTO itself. 15 The other circadian output kinase, CikA, also contributes directly to robustness of the PTO by enhancing rhythms under limiting concentrations of KaiA (16). Using the FP-PTO assay, we observed that addition of CikA moderately enhanced low amplitude rhythms under limiting concentrations of KaiA while shortening the period (Fig.…”
Section: Main Textmentioning
confidence: 86%
“…This structural similarity and binding competition raised the possibility that 15 SasA helps to regulate formation of the nighttime repressive complex, which is known to be restricted by (i) the phosphorylation state of the KaiC CII domain (13), (ii) the intrinsically slow rate of ATP hydrolysis by the KaiC CI domain (14,15), and (iii) the rare conversion of KaiB to the its fold-switched form that is competent to bind KaiC (11). Similarly, CikA and KaiA bind to the same site on the KaiBC complex (9), and this competition shortens the period (11) and 20 compensates for diminished concentrations of KaiA in the PTO in vitro (16), suggesting that output kinases fortify robustness of the PTO by modulating Kai protein interactions directly. 4 To explore how the intrinsic structural similarity between fold-switched KaiB and the N-terminal thioredoxin-like domain of SasA might influence the cyanobacterial PTO, we took advantage of a new high-throughput fluorescence polarization-based post-translational oscillator (FP-PTO) assay that reports on complex formation with KaiC in real time (17).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation